(untitled) (JIRE: Journal of Islamic Religious Education, 2025)
This article examines the relevance of the Islamic Religious Education (PAI) curriculum in addressing the challenges of cosmopolitan society, which is characterized by cultural diversity, ideological plurality, and often conflicting values with religious teachings. A cosmopolitan society demands an adaptive, contextual, and inclusive approach to religious instruction. This study employs a qualitative descriptive approach through literature review to analyze how the current PAI curriculum responds to these complexities and how it is implemented in classroom learning. The findings reveal that the curriculum remains largely normative and insufficiently responsive to contemporary issues such as tolerance, radicalism, multiculturalism, and digital identity. Therefore, it is essential to develop a transformative curriculum and dialogical learning strategies grounded in the social realities of cosmopolitan communities. The article recommends the integration of Islamic humanistic values into the PAI curriculum and pedagogy as an effort to shape a moderate, critical, and inclusive Muslim generation.